Effect of Rehabilitation Exercise Platform Core Muscles Therapy on Motor Function, Balance Function and Spinal Motion Range of Parkinson's Disease Patients - Jun XING; Yanjun WANG; Lizhuang ZHANG; Yahui WANG; Jianfang SUN; Lijing CHANG (康复学报)
Objective:To explore the effect of rehabilitation exercise platform core muscles therapy on motor function, balance function and spinal motion range of Parkinson's disease (PD) patients.Methods:82 PD patients were randomly assigned to the treatment group and control group, with 41 patients in each group. Both groups received routine drug treatment. The control group was added with exercise rehabilitation, including balance coordination of motion and training of gait and rhythm. The treatment group was added with exercise rehabilitation and rehabilitation exercise platform core muscles therapy 30 minutes each day for eight weeks. Unified Parkinson disease rating scale (UPDRS) was applied to evaluate motor function of patients, Berg balance scale (BBS) was applied to evaluate balance function, and the spine joint measurement of range of motion (ROM) was applied to evaluate torso posture activities range.Results:After eight week's therapy, the UPDRS scores were decreased (P<0.05), and the BBS scores were increased in both groups (P<0.05), the spine ROM was improved than that before treatment (P<0.05). There were significant differences between two groups in the UPDRS score, BBS score and spine ROM after eight week's therapy (P<0.05).Conclusion:Rehabilitation exercise platform core muscles therapy can improve motor function, balance function, spine ROM and daily activities of PD patients.